2014
DOI: 10.2169/internalmedicine.53.1502
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Dose of Acetaminophen as a Possible Risk Factor for Acute Kidney Injury: Learning from Two Healthy Young Adult Cases

Abstract: Acetaminophen overdose can lead to severe liver and kidney failure; however, the risk of therapeutic doses in healthy individuals causing acute kidney injury (AKI) is less clear. We herein describe the cases of two young adults with renal biopsy-proven acute tubular necrosis under a therapeutic dose of acetaminophen. The first patient exhibited mild reversible renal insufficiency, whereas, in the second case, the patient demonstrated a slightly increased serum creatinine level and enlarged kidneys and the admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 10 publications
2
20
0
Order By: Relevance
“…Moreover, there is evidence that the maximum recommended dose (i.e., 4 g/day) can induce mild to moderate hepatic cytolysis, even in healthy individuals (Watkins et al 2006;Winnike et al 2010). APAP can also induce acute kidney injury in some patients, either after poisoning or at therapeutic doses (Blakely and McDonald 1995;Kato et al 2014). APAP-induced acute nephrotoxicity manifests as acute tubular necrosis with oliguric renal failure, which can occur alone or in association with liver injury (Blakely and McDonald 1995;Jones and Prescott 1997).…”
Section: Acetaminophen (Apap)mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there is evidence that the maximum recommended dose (i.e., 4 g/day) can induce mild to moderate hepatic cytolysis, even in healthy individuals (Watkins et al 2006;Winnike et al 2010). APAP can also induce acute kidney injury in some patients, either after poisoning or at therapeutic doses (Blakely and McDonald 1995;Kato et al 2014). APAP-induced acute nephrotoxicity manifests as acute tubular necrosis with oliguric renal failure, which can occur alone or in association with liver injury (Blakely and McDonald 1995;Jones and Prescott 1997).…”
Section: Acetaminophen (Apap)mentioning
confidence: 99%
“…APAP can also induce acute kidney injury in some patients, either after poisoning or at therapeutic doses (Blakely and McDonald 1995; Kato et al. 2014). APAP‐induced acute nephrotoxicity manifests as acute tubular necrosis with oliguric renal failure, which can occur alone or in association with liver injury (Blakely and McDonald 1995; Jones and Prescott 1997).…”
Section: Introductionmentioning
confidence: 99%
“…TIN is also associated with autoimmune diseases such as Sjögren's syndrome and systemic lupus erythematosus, however, these diseases were ruled out in our case. To our knowledge, there have been only four adult cases including our own case of biopsy-confirmed TIN induced by a therapeutic dose of acetaminophen [5,13]. In the cases administrated several medications simultaneously it might be very difficult to specify the causative drug.…”
Section: Discussionmentioning
confidence: 94%
“…Although AKI is thought to be an extremely rare adverse effect of acetaminophen in healthy persons, therapeutic dose of acetaminophen sometimes impairs kidney function in patients who are glutathione depleted (chronic alcoholism, infants, starvation/fasting/malnutrition) or who take drugs that induce p450 proteins (smoking, isoniazid, chronic alcohol ingestion, anticonvulsants) [10]. It has been reported that therapeutic dose of acetaminophen sometimes induces both renal failure and hepatic failure [4,5], but such cases are uncommon. Cases of renal damage induced by a therapeutic dose of acetaminophen without liver damage is very rare and mostly limited to & Ryosuke Usui fzk11643@nifty.com children [6,7], and such cases have hardly ever been reported in adults.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was identified as a risk factor for acute renal injury [6] and it can cause onset of Stevens-Johnsons syndrome and toxic epidermal necrolysis [7,8]. Epidemiological studies revealed a link between the use of APAP during pregnancy and the incidence of attention deficit hyperactivity disorder (ADHD) and hyperkinetic disorder in children [9].…”
Section: Introductionmentioning
confidence: 99%